Agroforestry on runoff nitrogen and phosphorus losses from three paired watersheds after 25 years of implementation - Salceda-Gonzalez, Miguel; Udawatta, Ranjith P.; Anderson, Stephen H. (Agroforestry systems, 2024)
Non-point source pollution and agriculture have been correlated in a negative context. Conservation practices such as upland agroforestry buffers can help reduce the adverse impact of agriculture on water quality by reducing erosion and retaining nutrients in the fields. This study used a paired watershed approach to determine the effect of agroforestry buffers on runoff flow, total suspended solids (TSS), nitrate–nitrite (NN), total nitrogen (TN), and total phosphorus (TP) after 25 years of establishment and management. Linear models were developed for each parameter of interest during the treatment period and compared to previous models during the calibration period. Three paired watersheds were the subject of this study with a control watershed (no treatment), an agroforestry buffer (AB) watershed (trees + grasses), and a grass buffer (GB) watershed. The agroforestry watershed had 4.5 m wide buffers with [Pin Oak ( Quercus palustris Muenchh.), Swamp White Oak ( Q. bicolor Willd.), and Bur oak ( Q. macrocarpa Michx.) with Redtop ( Agrostis gigantea Roth), brome grass ( Bromus inermys Leyss.) and birdsfoot trefoil ( Lotus corniculatus L.)]. The grass buffer watershed had 4.5 m wide buffers with the same grasses planted in the agroforestry buffer watershed. The AB watershed had 62%, 25%, 64%, and 23% reductions in TSS, NN, TN, and TP losses, respectively, compared to the expected values without buffers. However, only NN and TN reductions were significant (ρ < 0.05). The GB watershed had 71%, 14%, and 33% lower TSS, NN, and TP losses than the expected values, no significant reductions were found. Even though the TSS reductions were not significant, they were greater than reductions reported on studies in the same watersheds in 1999 and 2008. The AB and GB watersheds had the greatest TN and TP reductions reported on these watersheds, respectively. Both watersheds had increased runoff compared to the calibration period due to unexpected inflow from surrounding areas. The results of this study show that upland agroforestry buffers can reduce sediment and nutrient losses long after their implementation and that it is worth to further study these types of long-term settings.